R & D Boost - New Sunday Star, Simrit Kaur (2008)
The Country's four research universiies have been allocated RM90.8mil each as additional funding under Buget 2009. Higher Education Minister Datuk Seri Mohd Khaled Nordin said tat would enable them to further strengthen their research and development capabilities.